EVALUATING THE EFFECTIVENESS OF TAX OBJECTION REVIEW IN INDONESIA’S TAX AUTHORITY - Trisnawati, Yuli; Nuryanah, Siti (UI Scholars Hub, 2022)
An evaluation of the effectiveness of tax objection review by the Directorate General of Taxes (DGT) is required due to the increasing number of tax disputes that continue to litigation and a low winning rate for DGT in tax court (approximately 40%). This study aims to analyze the effectiveness of reviewing tax objections at DGT using Campbell's Effectiveness Theory (1989) with criteria of programs and goals success, program satisfaction, inputs and outputs conformity, and overall goal achievement. This is case study research with a qualitative method presented in a descriptive analysis. Data was collected through documentation, interviews, and satisfaction surveys. Informants are from the DGT, Taxpayers, Tax Consultants, Tax Lecturers and the Secretariat of the Tax Supervisory Committee (Setkomwasjak). The results indicate that the tax objection review at the DGT has been moderately effective, as evidenced by the achievement of the predetermined targets. However, several criteria should be improved, such as input and output quality, workload and independence. The separation of the objection review unit from the Regional Office (Kanwil) of the DGT is one of the recommendations proposed to increase the independence of tax objection review.